A case study on manufacturing electronic-embedded garments with stitched surface-mount fabrication. (31st January 2022) - Islam Molla, Md Tahmidul; E Dunne, Lucy
Abstract: Electronic-embedded textiles or e-textiles preserve the form factor of typical apparel but have the ability to provide required electrical performance, enabling expanded functionality and comfort to the wearer. However, durable, reliable, and scalable manufacturing of e-textiles has remained one of the major challenges to large-scale development of garment-integrated applications of wearable technology. Moreover, there is a gap in our understanding of the impact of integration of electronics into textiles and challenges involved in manufacturing e-textile garments in mass. In this paper, we present the first manufacturing case study for electronic-embedded garments, to the best of our knowledge. We first developed a sensor-integrated fire-fighter turnout gear coat as an example e-textile product. Next, we performed a pre-production study to investigate the new variables that emerge from the prototyping phase to the production phase. To evaluate the challenges of manufacturing e-textiles in mass as compared to non-electronic garments, we produced 40 pieces each of regular and temperature sensing fire-fighter turnout gear coat liner garments using stitched surface-mount fabrication methods. The study results show that the average manufacturing time and cost to produce a sensor-integrated thermal liner are 3.27 and 3.44 times higher, respectively, than producing a regular thermal liner garment, given that all the materials, labor, and standard sewing methods and machines remain constant. Additionally, we show the impact on requisite worker skills and training and quality assurance methods to produce e-textile garments compared to regular garments. We illustrate high-potential areas where strategic product and production design that leverages existing machines and tools can reduce the impact that embedded technologies have on labor, equipment, and cost. We conclude that the stitched surface-mount manufacturing method could potentially be used as an alternative for manufacturing e-textiles in mass.